Adaptive changes of the autosomal part of the genome in a dioecious clade of Silene - Zluvova, Jitka; Kubat, Zdenek; Hobza, Roman; Janousek, Bohuslav (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2022)
The genus Silene brings many opportunities for the study of various processes involved in the evolution of dioecy and young sex chromosomes. Here we focus on a dioecious clade in Silene subgenus Silene and closely related species. This study provides improved support for monophyly of this clade (based on inclusion of further dioecious species) and a new estimate of its age (ca 2.3 million years). We observed a rise in adaptive evolution in the autosomal and pseudoautosomal parts of the genome on the branch where dioecy originated. This increase is not a result of the accumulation of sexually antagonistic genes in the pseudoautosomal region. It is also not caused by the coevolution of genes acting in mitochondria (despite the possibility that dioecy along this branch could have evolved from a nucleo-cytoplasmic male sterility-based system). After considering other possibilities, the most parsimonious explanation for the increase seen in the number of positively selected codons is the adaptive evolution of genes involved in the adaptation of the autosomal part of the genome to dioecy, as described in Charnov's sex-allocation theory. As the observed coincidence cannot prove causality, studies in other dioecious clades are necessary to allow the formation of general conclusions. This article is part of the theme issue 'Sex determination and sex chromosome evolution in land plants'.
Keywords: Chromosomes, Plant; Evolution, Molecular; molekulární evoluce; autosome evolution; sex chromosome; dioecy; Silene; chromozomy rostlin; Sex Chromosomes; Magnoliopsida; pohlavní chromozomy; genome evolution